Autonomous aggregation suppression by acidic residues explains why chaperones favour basic residues. (1st April 2020) - Houben, Bert; Michiels, Emiel; Ramakers, Meine; Konstantoulea, Katerina; Louros, Nikolaos; Verniers, Joffré; van der Kant, Rob; De Vleeschouwer, Matthias; Chicória, Nuno; Vanpoucke, Thomas; Gallardo, Rodrigo; Schymkowitz, Joost; et al.
Abstract: Many chaperones favour binding to hydrophobic sequences that are flanked by basic residues while disfavouring acidic residues. However, the origin of this bias in protein quality control remains poorly understood. Here, we show that while acidic residues are the most efficient aggregation inhibitors, they are also less compatible with globular protein structure than basic amino acids. As a result, while acidic residues allow for chaperone‐independent control of aggregation, their use is structurally limited. Conversely, we find that, while being more compatible with globular structure, basic residues are not sufficient to autonomously suppress protein aggregation. Using Hsp70, we show that chaperones with a bias towards basic residues are structurally adapted to prioritize aggregating sequences whose structural context forced the use of the less effective basic residues. The hypothesis that emerges from our analysis is that the bias of many chaperones for basic residues results from fundamental thermodynamic and kinetic constraints of globular structure. This also suggests the co‐evolution of basic residues and chaperones allowed for an expansion of structural variety in the protein universe. Synopsis: Charged gatekeeper residues attenuate short‐stretch‐mediated protein aggregation both kinetically and thermodynamically. An investigation of the aggregation‐breaking characteristics of the charged residues offers novel insight into the molecular basis for aggregation breaking, the structural compatibility of charged residues with the native fold and their interactions with the proteostatic machinery. Acidic residues are more potent aggregation breakers than basic ones, owing both to their shorter sidechain lengths and the specific characteristics of the charge‐carrying carboxyl moiety. Acidic residues are less compatible with globular protein structure than positive ones, limiting their use as aggregation gatekeepers. DnaK, the Escherichia coli Hsp70 ortholog, specifically binds basic residues and compensates for their poorer aggregation‐breaking potential. DnaK recognizes basic residues by the same characteristics that make them poor aggregation breakers, yet more structurally compatible. These results hint towards a co‐evolution of basic residues and chaperones which allowed for increased structural variety in the protein universe, in line with the pre‐biotic reduced‐alphabet hypothesis. Abstract : Stronger aggregation propensities explain why chaperones have evolved to favour hydrophobic sequences flanked by basic residues, despite them being more compatible with globular protein structure than acidic‐residue gatekeeper sequences.